Zimbabwe: The Blame Game - Mwanaka, Tendai R. (Book collections on Project MUSE., 2013)
The Blame Game is a cycle of creative non-fiction pieces, pulling the readers through the politics of modern day Zimbabwe. Like in any game, there are players in this game, opposing each other. The game is told through the eyes of one of the players, thus it is subjective. It centres on truthfully trying to find who to blame for Zimbabwe's problems, and how to undo all these problems. Finding who to blame should be the beginning for the search of solutions. It encourages talking to each other, maybe about the wrongs we have done to each other, and genuinely trying to embrace and forgive each other. In trying to undo the problems in Zimbabwe, it also offers insight or solutions on a larger platform - Africa: particularly South Africa; that it might learn from other African countries that have imploded before it, how to solve its own problems.